Defeating SQL Injection. - Shar, Lwin Khin; Tan, Hee Beng Kuan (Computer (00189162), 2013)
The best strategy for combating SQL injection, which has emerged as the most widespread website security risk, calls for integrating defensive coding practices with both vulnerability detection and runtime attack prevention methods.